Math, asked by superstat12, 1 year ago

using remainder theorem check whether​

Attachments:

Answers

Answered by MeetDattani
0

Step-by-step explanation:

g(x) = 2x+1

= 2x+1=0

= 2x= -1

= X= -1/2

p(x)= 2x^3-11x^2-4x+5

p(-1/2)=2×(-1/2)^3-11×(-1/2)^2-4×(-1/2)+5

= 2×(-1/8)-11×(1/4)-1+5

= -2/8-11/4+4

= -1/4-11/4+4

= -1-11+16/4

= 4/4

= 1

HOPE IT WOULD HELP YOU

PLEASE MARK ME BRAINLIEST

Answered by αηυяαg
3

Step-by-step explanation:

g(x) = 2x+1

= 2x+1=0

= 2x= -1

= X= -1/2

p(x)= 2x^3-11x^2-4x+5

p(-1/2)=2×(-1/2)^3-11×(-1/2)^2-4×(-1/2)+5

= 2×(-1/8)-11×(1/4)-1+5

= -2/8-11/4+4

= -1/4-11/4+4

= -1-11+16/4

= 4/4

= 1

HOPE IT WOULD HELP YOU

PLEASE MARK ME BRAINLIEST

Similar questions